FinTech integration in the financial management of Islamic social enterprises - Nurul Aini Muhamed; Muhammad Iqmal Hisham Kamaruddin; Sofiah Md Auzair; Saunah Zainon (Virtus Interpress, 2025)
Indexed Publication (Tier 2)